LEMBAGA JAMINAN FIDUSIA DALAM PERJANJIAN PEMBIAYAAN KONSUMEN - Sitti Nurjannah (Jurusan Ilmu Hukum Fakultas Syariah dan Hukum uin alauddin, 2016)
Vehicle financing agreement was made as the embodiment of the financing agreement between the company and consumer. However, motor vehicle financing agreement with this fiduciary standard contains clauses that contain rights and obligations of each party and made by one party, namely finance companies, consumers are only given an alternative choice